Transfer pricing and corporate taxation : Problems, practical implications and proposed solutions / Elizabeth A. King - King, Elizabeth A.
Transfer pricing is often identified as the most important tax issue that multinational corporations face. This publication is an extremely useful tool for practitioners and tax directors grappling with complex and contentious transfer pricing issues of various kinds. It contains a series of highly detailed case studies, which draw on the author's two decades as a government economist specializing in transfer pricing and valuation, a transfer pricing economist with Price Waterhouse, and, lastly, an independent consultant. These case studies elucidate the types of intercompany transactions that tax authorities often scrutinize, lay out how one should go about analyzing such transactions under the existing regulatory regime in considerable detail, and illustrate a number of proposed alternative approaches that could substantially reduce compliance costs and the frequency of transfer pricing disputes.